The freeze on mass media campaigns in England: a natural experiment of the impact of tobacco control campaigns on quitting behaviour. (16th January 2014) - Langley, Tessa; Szatkowski, Lisa; Lewis, Sarah; McNeill, Ann; Gilmore, Anna B.; Salway, Ruth; Sims, Michelle
Abstract Aims To measure the impact of the suspension of tobacco control mass media campaigns in England in April 2010 on measures of smoking cessation behaviour. Design Interrupted time series design using routinely collected population‐level data. Analysis of use of a range of types of smoking cessation support using segmented negative binomial regression. Setting England. Measurements Use of non‐intensive support: monthly calls to the National Health Service (NHS) quitline (April 2005–September 2011), text requests for quit support packs (December 2007–10) and web hits on the national smoking cessation website (January 2009–March 2011). Use of intensive cessation support: quarterly data on the number of people setting a quit date and 4‐week quitters at the NHS Stop Smoking Services (SSS) (quarter 1, 2001 and quarter 3, 2011). Findings During the suspension of tobacco control mass media spending, literature requests fell by 98% [95% confidence interval (CI) = 96–99], and quitline calls and web hits fell by 65% (95% CI = 43–79) and 34% (95% CI: 11–50), respectively. The number of people setting a quit date and 4‐week quitters at the SSS increased throughout the study period. Conclusions The suspension of tobacco control mass media campaigns in England in 2012 appeared to markedly reduce the use of smoking cessation literature, quitline calls and hits on the national smoking cessation website, but did not affect attendance at the Stop Smoking Services. Within a comprehensive tobacco control programme, mass media campaigns can play an important role in maximizing quitting activity.